Peran Sultan/ah di Kesultanan Aceh Darussalam dalam Perniagaan Jalur Maritim Tahun 1596 - 1675 M - Cholifiah, Alifa; Sanusi, Anwar; Padiatra, Aditia Muara (Historia Madania: Jurnal Ilmu Sejarah, 2024)
Spices and Ports are two things that cannot be separated in the commercial transformation that occurred centuries ago. The two are related to each other and form a knot that is interdependent and gives rise to various reactions and ambitions that occur among every noble and ruler who wants to control commerce. This is also related to various trading ports in Indonesia such as Sriwijaya, Pasai, and Malacca. The fall of Malacca into the hands of the Portuguese resulted in a shift in trade routes directed to the Red Sea, this was seriously used by the Sultanate of Aceh Darussalam to seize international scale trade. So this research aims to present a reconstruction of maritime trade routes that occurred in the territory of the Sultanate of Aceh Darussalam so that it discusses trade routes, commodities and even payment instruments used in each of these periods and how the policies of each sultan/ah in the Aceh Darussalam Sultanate towards trade routes maritime events that occurred in the 17th century AD. The research method used is the historical research method which consists of 4 stages, namely heuristics, criticism, interpretation, and historiography. This research resulted in the trading routes of the Sultanate of Aceh Darussalam, trade commodities such as pepper, oil, tin, policies and regulations that apply in regulating trade mobilityÂ including means of payment in the form of deureuham, ketun, and Spanish ringgit as well as the role of the sultan/ah in establishing trade policies to obtain a lot of advantages such as rising pepper prices (Iskandar Muda era), diplomacy with England (during Al-Mukamil), tin monopoly on silver (during Sultanah Safiatuddin's time).Keywords: Commerce, Maritime, Sultan/ah, Aceh Darussalam